PENGEMBANGAN PERANGKAT KONVERSI ENERGI PANAS MENJADI ENERGI LISTRIK - Selamat Ependi; Nengah Maharta; Eko Suyanto (Jurnal Pembelajaran Fisika, 2016)
The purpose of this developmental research was to elaborate a thermal energy into electrical energy converter device with the user manual for physics learning of electrical energy resources. The method of this research was research and development (R D) based on Suyanto, the steps that conducted comprise of need analysis, identification of sources power, identification of product specifications, product development, product testing, and the final production. Based on the test result, it was known that product has specifications: the correlatoin sensitivity of raising the temperature to the voltage is 0.702 mV/C; to the electrical current is 0.035 mA/C; and to the electrical power is 10.927 mW/C. The results of the feasibility test of thermal energy into electrical energy converter device with the user manual showed that the product is proper to use by the score of 3.692 on the physical eligibility test and 2.667 on the test design experts.Tujuan penelitian pengembangan ini adalah mengembangkan alat konversi energi panas menjadi energi listrik beserta petunjuk penggunaannya untuk pembelajaran fisika materi sumber energi listrik. Metode penelitian ini adalah penelitian dan pengembangan menurut Suyanto, tahapan yang dilakukan meliputi analisis kebutuhan, identifikasi sumber daya, identifikasi spesifikasi produk, pengembangan produk, uji produk, dan produksi akhir. Berdasarkan hasil uji yang telah dilakukan, diketahui spesifikasi produk yaitu: sensitivitas hubungan antara peningkatan suhu terhadap tegangan sebesar 0,702 mV/C; terhadap arus listrik sebesar 0,035 mA/C; dan terhadap daya listrik sebesar 10,927 mW/C. Hasil Uji kelayakan alat konversi energi panas menjadi energi listrik dan user manual menyatakan bahwa produk layak untuk digunakan dengan skor 3,692 pada uji kelayakan fisik dan skor 2,667 pada uji ahli desain.Kata kunci: energi listrik, energi panas, konversi energi, pengembangan.